2011
DOI: 10.1093/heapol/czr032
|View full text |Cite
|
Sign up to set email alerts
|

Household perceptions and their implications for enrolment in the National Health Insurance Scheme in Ghana

Abstract: Perceptions related to providers, schemes and community attributes play an important role, albeit to a varying extent in household decisions to voluntarily enroll and remain enrolled in insurance schemes. Scheme factors are of key importance. Policy makers need to recognize household perceptions as potential barriers or enablers to enrollment and invest in understanding them in their design of interventions to stimulate enrollment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
159
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(194 citation statements)
references
References 32 publications
32
159
3
Order By: Relevance
“…Our findings are similar to those of other studies in Nigeria, Ghana and South-Africa where the type of facility was found to influence prompt attention: the public providers performed poorly in the domain of prompt attention compared to private providers [25,26,29]. Several studies explain that the poor performance of public providers is attributable to giving patients an appointment for a particular day without a specific patient consultation time [25], high patient numbers exceeding the capacity of public facilities [25], poor quality of public services [30], especially poor attitude of providers versus the insured-users and bad interpersonal relationships [17,29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are similar to those of other studies in Nigeria, Ghana and South-Africa where the type of facility was found to influence prompt attention: the public providers performed poorly in the domain of prompt attention compared to private providers [25,26,29]. Several studies explain that the poor performance of public providers is attributable to giving patients an appointment for a particular day without a specific patient consultation time [25], high patient numbers exceeding the capacity of public facilities [25], poor quality of public services [30], especially poor attitude of providers versus the insured-users and bad interpersonal relationships [17,29].…”
Section: Discussionsupporting
confidence: 90%
“…Here, j refers to the level of the response variable, with j = 1 as the reference category. Since it is common for one or more β ’s to differ across values of j, we applied a more flexible model that fits three special cases of the generalized model: the proportional odds model, the partial proportional odds model, and the logistic regression model [27-29]. This model is presented by:…”
Section: Methodsmentioning
confidence: 99%
“…Whether SHI and CBHI have the same potential impact in settings other than those where the studies were conducted is highly dependent on a particular country's socioeconomic, cultural and political context. 2,12,38,[42][43][44] This is illustrated by the few studies that showed negative impacts of SHI and CBHI on certain domains. Similarly, the review does not provide an answer to the question of whether SHI, CBHI or PHI is the optimal type of health financing mechanism, or of how it compares with tax-based systems -this is also highly dependent on context.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Further, the NHIS insurance premiums are supposed to be structured based on individual or household's ability to pay. However, due to the large informal sector and corresponding difficulties in assessing income and living standards of informal sector households, flat rate insurance premiums are charged by the NHIS at the district schemes (Abiiro & McIntyre, 2013;Jehu-Appiah, Aryeetey, Spaan, Agyepong, & Baltussen, 2010). To relieve the poor and vulnerable of the burden of the flat rate insurance premiums, the indigent are exempted from paying insurance premiums by providing them with government subsidies.…”
Section: Introductionmentioning
confidence: 99%